Meningkatkan Akses Transportasi Untuk Masyarakat Pedesaan: Tantangan Dan Solusi - Muhammad Viki Baihaki; Bintang Ramadhan; Putra Fajar Aditya; Zahra Namiya Fitri; Siti Sahara (Peneliti.net, 2023)
This article discusses challenges and solutions in improving transportation access for rural communities. These challenges include limited transportation infrastructure, limited access to public transportation services, limited access to private vehicles, and lack of driver skills. To solve the problem, the government can invest in transportation infrastructure, expand transportation service networks to rural areas, provide special financing schemes for private vehicles, and provide driver skills training. Thus, it is hoped that transportation access for rural communities can be improved and their quality of life can improve..